RADI-23. CLINICAL RISK ASSESSMENT SCORE TO ESTIMATE THE LIKELIHOOD OF PSEUDOPROGRESSION VERSUS TUMOR RECURRENCE FOLLOWING STEREOTACTIC RADIOSURGERY FOR BRAIN METASTASES. (12th August 2019) - Skeie, Bente Sandvei; Enger, Per Øyvind; Pedersen, Paal-Henning; Skeie, Geir Olve
Abstract: OBJECTIVE: A major challenge in the follow-up of patients managed with stereotactic radiosurgery (SRS) for brain metastases (BM) is to differentiate pseudoprogression (PP) from tumor recurrence (TR). A clinical score based on tumor and treatment related factors would be valuable when selecting appropriate treatment. MATERIAL AND METHODS: Follow-up images of 97 consecutive patients treated with SRS for 406 BM were analyzed. Of these 100 (24.6 %) BM in 48 (49.5 %) patients responded either with TR (delayed growth; 53 (13.1 %) BM) or PP (temporary volume increase; 47 (11.6 %) BM). Differences between the 2 groups were analyzed and used to develop a PP risk assessment score (PP-RAS). RESULTS: Significant factors associated with a higher incidence of PP versus TR were: primary lung cancer vs. other primaries, BM volume ≤ 2cc (or BM ≤ 1.5 cm in diameter), Target cover ratio > 98 % and prior radiation SRS or WBRT. Based on the presence (0) or not (1) of these 5 parameters, a risk assessment score for PP versus TR was established. A PP-RAS score of 0 corresponds with high likelihood of PP vs. TR, whereas a score of 5 corresponds with a high risk of TR. A score of ≤ 1 point was associated with 100 % PP, 2 points with 57 % PP and 43 % TR, 3 points with 57 % TR and 43 % PP, whereas ≥ 4 points were associated with 84 % TR and 16 % PP, π=24.57, df =4, p < 0.001). CONCLUSION: Based on these 5 parameters at the time of SRS our risk assessment score could robustly differentiate between PP versus growth following SRS. The score is user-friendly and may be a useful tool to guide the decision making whether to retreat or observe at appropriate follow-up intervals.